Comparison of Lower Extremities Physical Performance on Male Young Adult Athletes with Normal Foot and Flatfoot - Kumala, Mira Saraswita; Tinduh, Damayanti; Poerwandari, Dewi (Surabaya Physical Medicine and Rehabilitation Journal, 2019)
Background: Motor tasks involving the lower legs activate a closed kinetic chain, with the foot being the terminal part of that chain. It is known that when a part of this chain is disturbed, it will affect other parts of the chain, including the effect on the motor performance of lower extremities.Aims: To see the difference of physical performance on athlete age 14 – 17 years with flatfoot and normal foot on strength, balance and agility factors.Methods: Male athletes age 14 – 17 years enrolled in Sport Senior High School at Sidoarjo who underwent athletes screening at Sport Clinic of dr. Soetomo General Hospital and fulfill the inclusion criteria. The subject were 29 boys, the normal foot were 22 boys and the flatfoot were 7 boys. Subjects were examined for Clarke's angle and Chippaux-Smirak index to diagnose flatfoot and did Single-leg Hop for Distance, One Leg Test, Star Excursion Balance Test, and Hexagon Hop Test.Result: The statistical analysis showed no difference of lower extremities' physical performance in strength using Single-leg Hop for Distance (p>0.05), balance using One Leg Test and Star Excursion Balance Test (p>0.05), and agility using Hexagon Hop Test (p>0.05) on male athletes age 14-17 years with normal foot and flatfoot.Conclusion: There are no difference of lower extremities' physical performance in strength, balance and agility on male athlete age 14-17 years with normal foot and flatfoot.